2009
DOI: 10.1097/aco.0b013e32832f3320
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and regional anesthesia

Abstract: The explosion of sedation well beyond the world of regional anesthesia has raised new challenges. Some sedative procedures will be performed more and more often by nonanesthesiologists in the future. This trend is inevitable due to limited resources and stresses on the importance of building up education and teaching programs for nonanesthesiologists. The need for reliable devices for monitoring of sedation and new hypnotics, which have even better phamacokinetics than those available, are needed to match the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
2
7
0
2
Order By: Relevance
“…It would be clinically advantageous for proper sedation with minimal side effects if the individual propofol Ce value incorporated with covariates rather than its average Ce of some population could be achieved. Yang showed that the decrease in propofol requirements for sedation during spinal anaesthesia was influenced by the block height, but not by the dose of local anaesthetic used [2]. This result is consistent with our established pharmacodynamic model in which the sensory block level rather than the dose of bupivacaine was proven to be a significant covariate.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It would be clinically advantageous for proper sedation with minimal side effects if the individual propofol Ce value incorporated with covariates rather than its average Ce of some population could be achieved. Yang showed that the decrease in propofol requirements for sedation during spinal anaesthesia was influenced by the block height, but not by the dose of local anaesthetic used [2]. This result is consistent with our established pharmacodynamic model in which the sensory block level rather than the dose of bupivacaine was proven to be a significant covariate.…”
Section: Discussionsupporting
confidence: 85%
“…Yang showed that the decrease in propofol requirements for sedation during spinal anaesthesia was influenced by the block height, but not by the dose of local anaesthetic used . This result is consistent with our established pharmacodynamic model in which the sensory block level rather than the dose of bupivacaine was proven to be a significant covariate.…”
Section: Discussionsupporting
confidence: 84%
“…Rapid modifications could have been better controlled with the use of target-controlled infusion, where the administration is driven by microprocessor-controlled algorithms based on pharmacokinetic models. [ 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…During the surgical procedure under regional anaesthesia, sedation is provided for patient comfort. To achieve adequate sedation without any haemodynamic or respiratory side effects, a state called conscious sedation is necessary . Conscious sedation is defined as a state of depressed consciousness using a sedative drug during which the patient should be able to respond to verbal command.…”
mentioning
confidence: 99%